Dynamic selection of visible wavelengths using resonant TiO2 nanostructures - Um Han-Don; Choi Deokjae; Solanki Amit; Huang Emerald; Seo Kwanyong; Habbal Fawwaz (Nanophotonics)
All-dielectric nanoarrays have strong electromagnetic resonances with various interesting applications and are tuned by adjusting their geometrical parameters. However, their optical properties are permanently encoded during fabrication. This study presents robust dynamically tunable all-dielectric nanoresonators for controllable, reversible, and reproducible color filtering. Our design uses an array of TiO2 nanodiscs embedded in a transparent, stretchable polydimethylsiloxane (PDMS) membrane and exhibits a narrow spectral response due to Mie magnetic and electric dipole resonances hybridized with the TiO2 nanodiscs lattice modes. By mechanically stretching the PDMS membrane, the pitch of the TiO2 nanodiscs was increased and the spectral location of the resonances was altered. Additionally, an optically asymmetric structure was fabricated by partially embedding TiO2 nanodiscs in PDMS. Thus, the magnitude of the Rayleigh anomaly diffraction, which could interrupt the dipole resonances, was reduced. Our design has sharp, frequency-tunable resonances in the visible spectrum, and we demonstrated dynamic tunability by stretching the metasurfaces.